Examining the influence of perceived need on the adoption of information system in public hospitals in Yemen - Adnan Mukred; Dalbir Singh; Nurhizam Safie Mohd Satar (Penerbit Universiti Kebangsaan Malaysia, 2020)
The importance of perceived need in the health sector, specifically its influence on health workers’ behaviour towards the adoption of an information system (IS), needs to be better understood. Therefore, the purpose of the present study was to investigate the extent to which a perceived need factor influences physicians’ and nurses’ behaviour to adopt IS in public hospitals of Yemen. The data were collected from two public hospitals in Yemen using a self-administered questionnaire. The study suggests that the proposed model is able to investigate The impact of perceived need factor on the adoption of IS through the UTAUT model in public hospitals of developing countries. The findings of this research revealed that the social influence, the perceived need for IS and its benefits and the effort expectancy have significant effects on the physicians’ and nurses’ behavioural intentions to adopt IS. However, facilitating conditions does not have any substantial consequence on their behavioural intentions.